The subject supposed to design. Issue 1 (2nd January 2017) - Tie, Warwick John
Abstract: A new figure emerges within participatory design, that of a user subject, who not only participates in design processes, but who is to subsequently design-in-use on their own. Like 'the subject supposed to know', identified by Jacques Lacan as central to the contemporary production of knowledge, this subject is susceptible to both administrative regulation and to forms of hegemonic power its social design projects might trigger. Characterising this subject's current response to such situations are various attempts to develop in a 'reflexive' manner. This reaction appears, however, to sustain the subject supposed to design in a state of political vulnerability. Alternatively, potential exists for the subject to avoid these outcomes where its social projects are re-sculpted in a 'reflective' manner: in keeping with dialectical contradictions which spring open as decision 'points' between the explanatory, diagnostic and normative semblances of design objects approached as 'design Things'. The situation of the Land and Water Forum of Aotearoa New Zealand illustrates these matters.